Can customer relationships backfire? How relationship norms shape moral obligation in cancelation behavior - Shuqair, Saleh (2022)
Shuqair, S., Costa Pinto, D., Cruz-jesus, F., Mattila, A. S., Guerreiro, P. D. F., & So, K. K. F. (2022). Can customer relationships backfire? How relationship norms shape moral obligation in cancelation behavior. Journal of Business Research, 151(November), 463-472. https://doi.org/10.1016/j.jbusres.2022.07.008 ------ Funding: The authors Diego and Frederico gratefully acknowledge financial support from FCT Fundação para a Ciência e a Tecnologia (Portugal), national funding through research grant Information Management Research Center – MagIC/NOVA IMS (UIDB/04152/2020).